Using the visual-world paradigm to explore the meaning of conditionals in natural language. Issue 8 (14th September 2018) - Zhan, Likan; Zhou, Peng; Crain, Stephen
ABSTRACT: This paper reports three eye-tracking experiments using the visual world paradigm to explore the meaning of conditionals in Mandarin Chinese. Experiment 1 found that, when all the tokens were actually true in the experimental setting, the conditional connective if  …  then …  didn't elicit significantly more anticipatory fixations than the conjunctive connective  … and …  on a token that is appropriately to be merged by the sentential connectives. By contrast, Experiments 2 and 3 found that, when a token was designed as hypothetically but not actually true in the experimental setting, the conditional connective elicited significantly more anticipatory fixations than the conjunctive connective on this hypothetical token. The implications of the experimental paradigm and the observed results were then discussed in relation to theories of conditionals, and to models of rationality in general.